Fracture toughness and fatigue crack behaviour of A3003/SUS304 lap friction stir welded joints*. Issue 4 (3rd April 2017) - Nishida, Hidehito; Ogura, Tomo; Hatano, Ryoichi; Kurashima, Hirotaka; Fujimoto, Misuo; Hirose, Akio
Abstract: Friction stir welding (FSW) can weld dissimilar metal joints without a thick and brittle intermetallic compound layer at the weld interface. In this study, the dissimilar lap joint of A3003 aluminium alloy and SUS304 stainless steel was successfully welded by FSW, and the joint obtained was tested to examine the properties of fracture toughness and fatigue crack growth rate. Its fracture toughness was different by the directions of crack propagation. The fracture toughness of advancing side (AS) to retreating side (RS) was stronger than that of RS to AS, and that of cryogenic temperature was stronger than that of room temperature. Its fatigue crack growth rate also showed the same tendency as its fracture toughness. These data were compared with the past data and discussed.